2018
DOI: 10.1111/1365-2664.13140
|View full text |Cite
|
Sign up to set email alerts
|

The importance of individual heterogeneity for interpreting faecal glucocorticoid metabolite levels in wildlife studies

Abstract: As a non‐invasive and inexpensive method, the use of faecal glucocorticoid metabolites (FGM) analysis in wildlife research is increasing. Various environmental factors have been shown to influence FGM levels, or faecal corticosteroid metabolites (FCM) levels in birds, but most studies do not account for inter‐individual variance, which we hypothesized may substantially affect results. We combined FCM analysis with genetic analysis to identify the sex and individual's identity in samples collected in three cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 71 publications
3
22
0
Order By: Relevance
“…Non-invasive genetic sampling methods have become widely used in genetic studies and have been shown to be a reliable approach for genetic studies in reindeer [28,29,30]. It has also been shown that combining genetic analysis with FCM measurements is a useful approach to document individuals and their sex, and that ignoring this information could lead to erroneous conclusions when addressing stress levels in animal populations [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive genetic sampling methods have become widely used in genetic studies and have been shown to be a reliable approach for genetic studies in reindeer [28,29,30]. It has also been shown that combining genetic analysis with FCM measurements is a useful approach to document individuals and their sex, and that ignoring this information could lead to erroneous conclusions when addressing stress levels in animal populations [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…That could be particularly true in our case, since the ASAP rescue center purposely welcomes parrots coming from various origins and backgrounds, notably with different stress or welfare histories. Additionally, different coping styles, bacterial gut flora, and individual genetic heterogeneity have been proposed among other factors to explain the commonly observed inter-individual variations [ 37 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have quantified seasonal patterns in stress within and among individuals. A study of the capercaillie ( Tetrao urogallus ), a non-migratory grouse, found that sex and individual identity accounted for as much as 37% of variation in stress among free-living individuals, while environmental variables accounted for only 5.1% of the variation ( Coppes et al. , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2018 ). By identifying individuals, Coppes et al (2018 ) detected strong, sex-specific, seasonal variation within individuals, highlighting the need to track stress in known individuals, especially when individuals are non-territorial and share common habitat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation